Lost and found: Frogs in a biodiversity hotspot rediscovered with environmental DNA - Carla Martins Lopes; Délio Baêta; Alice Valentini; Mariana Lúcio Lyra; Ariadne Fares Sabbag; João Luiz Gasparini; Tony Dejean; Célio Fernando Baptista Haddad; Kelly Raquel Zamudio (Molecular Ecology, 2021)
Declines and extinctions are increasing globally and challenge conservationists to keep pace with biodiversity monitoring. Organisms leave DNA traces in the environment, e.g., in soil, water, and air. These DNA traces are referred to as environmental DNA (eDNA). The analysis of eDNA is a highly sensitive method with the potential to rapidly assess local diversity and the status of threatened species. We searched for DNA traces of 30 target amphibian species of conservation concern, at different levels of threat, using an environmental DNA metabarcoding approach, together with an extensive sequence reference database to analyse water samples from six montane sites in the Atlantic Coastal Forest and adjacent Cerrado grasslands of Brazil. We successfully detected DNA traces of four declined species ( Hylodes ornatus , Hylodes regius , Crossodactylus timbuhy , and Vitreorana eurygnatha ); two locally disappeared ( Phasmahyla exilis and Phasmahyla guttata ); and one species that has not been seen since 1968 (putatively assigned to Megaelosia bocainensis ). We confirm the presence of species undetected by traditional methods, underscoring the efficacy of eDNA metabarcoding for biodiversity monitoring at low population densities, especially in megadiverse tropical sites. Our results support the potential application of eDNA in conservation biology, to evaluate persistence and distribution of threatened species in surveyed habitats or sites, and improve accuracy of red lists, especially for species undetected over long periods.